PENERAPAN CONCEPTUAL CHANGE MODEL UNTUK MEREDUKSI MISKONSEPSI SISWA PADA MATERI SUHU DAN KALOR - Dedi, Dedi; S, Stepanus Sahala; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to known effectiveness the application of conceptual change model to reduce students? misconceptions on heat and temperature in SMA Negeri 2 Teluk Keramat. Pre-experimental design with one group pretest-posttest design used in this research. Sample of this research was students from XI IPAclass (n = 37) who choosen by saturated  sampling technique. Diagnostic test which consisted of 18 multiple choice question with open reasoning.Based on the results of data analysis found the findings, as follows: (1) the percentage of students? misconceptions before and after being given remedial learning each 63,36% and 18,01%; (2) the average decrease of misconceptions equal to 45,35%; (3) There was a significant conceptual change (  50,7;  1;  0,05) after being given remedial learning; and (4) The level effectiveness of remediation is high (DQM= 71,57%).Based on these results, it is expected that conceptual change model can be used as an alternative remediation activities to reduce misconception. Keywords:       Misconception, Remediation, Conceptual Change Model, Heat and Temperature